MOTIVATION AND FUTURE CHOICE IN EDUCATIONAL STRATEGIES OF YOUTH - Ekaterina S. Popova (Moscow Polytechnic University, 2016)
Statistics shows that there are both quantitative and qualitative changes in the area of general and vocational education. These changes have an impact on the future educational strategies andchoice. What are school graduates going to do? Where and why have they decided to continue education? What do they consider as the most important in life and what do they want to achieve? The paper presents the preliminary results of the study «New meanings in the educational strategies of youth» (2013), which is a part of the longitudinal study of the dynamics of educational trajectories of young people based on comparable research data among high school graduates of the Novosibirsk region from 1960s to 2010s.